ENERFUND - Identifying and rating deep renovation opportunities - Geissler, Susanne; Androutsopoulos, Andreas; Charalambides, Alexandros G.; Jareno Escudero, Cristina; Jensen, O. M.; Kyriacou, Orestis; Petran, Horia (My University, 2019)
European Directive (EU) 2018/844 amending Directives 2010/31/EU (EPBD) and 2012/27/EU (EED) aims at decarbonizing the European building stock. Energy efficiency measures and renewable energy use play an important role, especially regarding retrofit of existing buildings. Identification of retrofit opportunities and aggregation of projects to benefit from economy of scale are a precondition for the implementation of large-scale renovation projects. The ENERFUND project, funded by the HORIZON 2020 programme, provides data from Energy Performance Certificates according to EPBD publicly available in the form of a map and combines them with other geo-referenced data and general information to allow for the rating of deep renovation and carbon reduction opportunities. In this way, the tool assists in identifying retrofit opportunities and aggregation of projects for financing. It also assists in supply-side energy spatial planning, because it shows where energy consumption is likely to decrease due to economic renovation potentials. This contribution shows an overview of data available for thirteen European Member States. Data sources and differences regarding the type of data are explained, and challenges such as data quality issues and data protection concerns are discussed. It is demonstrated that the ENERFUND tool certainly assists in decarbonizing the European building stock, although some improvements are still necessary.
Keywords: Energy utilization; Retrofitting; Sustainable development; Energy efficiency; Economy of scale; Efficiency measure; Energy performance; European directive; Renewable energy use; Retrofit of existing buildings; Spatial planning